Diaphragm dysfunction, lung aeration loss and weaning-induced pulmonary oedema in difficult-to-wean patients - Dres, Martin (Ann Intensive Care, 2021)
BACKGROUND: Diaphragm dysfunction and weaning-induced pulmonary oedema are commonly involved during weaning failure, but their physiological interactions have been poorly reported. Our hypothesis was that diaphragm dysfunction is not particularly associated with weaning-induced pulmonary oedema. METHODS: It was a single-centre and physiological study conducted in patients who had failed a first spontaneous breathing trial and who underwent a second trial. The diaphragm function was evaluated by measuring the tracheal pressure generated in response to a bilateral magnetic phrenic nerves stimulations. Weaning-induced pulmonary oedema was diagnosed in case of failure of the spontaneous breathing trial if patients exhibited signs of plasma concentration or echocardiographic diagnosis of pulmonary artery occlusion pressure elevation. RESULTS: Fifty-three patients were included and 31/53 (58%) failed the spontaneous breathing trial, including 24/31 (77%) patients with weaning-induced pulmonary oedema. Diaphragm dysfunction was present in 33/53 (62%) patients. Diaphragm dysfunction or weaning-induced pulmonary oedema were present in 26/31 (84%) of the patients who failed the spontaneous breathing trial. Weaning-induced pulmonary oedema occurred in 20/33 (61%) patients with a diaphragm dysfunction and in 4/20 (20%) patients without (p = 0.005). CONCLUSION: Weaning-induced pulmonary oedema was three times more frequent in case of diaphragm dysfunction. Even in case of diaphragm dysfunction, physicians might be encouraged to investigate the presence of weaning-induced pulmonary oedema during weaning failure.